Conflict management in the workplace: the superior secretary perspectives - Akpomudjere, Ovwiroro (Journal of Professional Secretaries and Office Administrators, 2014)
Conflicts among people who work together are inevitable. Most conflicts however, are not only unpleasant, but also unproductive. While occasional conflicts can lead to an exploration of and solution to problem, it is more often an expression of petty differences for which no real solution exists. An effective team thrives on cooperation, and conflict makes cooperation difficult if not impossible. Supervisor – secretary conflict can be either work-related or interpersonal. Both kinds require attention. This paper posits that a supervisor and secretary need to develop team spirit if they are to be fully effective. This paper discusses the concept of conflict, conflict management, causes of conflict and characteristics of mutual support and good communication. It recommends among others that supervisor and secretary should give mutual support to one another in executing their roles in the work place for the overall benefit of the organisation.